Exploring the factors that lead the adoption of virtual reality technologies among football fans - Souto, D.; Oliveira, P.; Loureiro, S. M. C. (2020 Global Marketing Conference at Seoul Proceedings, 2020)
Virtual Reality (VR) applications are growing into an increasing market size, with VR technologies being used in manufacturing, medicine, art, navigation, education and gaming (Loureiro, Guerreiro, Eloy, Langaro & Panchapakesan, 2019). In sports industry, the adoption of VR is still in a very early stage, despite being acknowledged as a promising technology for various applications, among them, improving fans´ experience while watching sports games (Kim & Ko, 2019).